Retrospective Study Of Seroprevalence Of Transfusion Transmissible Infections Among Blood Donors In A Tertiary Care Centre In Thane District Of Maharashtra (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Blood transfusion is an integral part of health care as well as one of the life saving  procedure. But it carries risk of certain infections, especially viral, known as transfusion  transmissible infections (TTIs). Aim: To study seroprevalence of TTIs (HIV, HBsAg, HCV, and syphilis & malaria) in a tertiary care  centre in Thane district of Maharashtra. Study design: Hospital based retrospective observational study Methodology: The retrospective study was conducted by accumulating and analysing the data regarding  TTIs from blood bank records. Total 20270 blood units were collected in 10 years period  from January 2010 to December 2019. All blood units were screened by respective  immunological methods. Results: On analysis of the data of all screened blood units, it was observed that 89 tested positive  for HIV (0.44%), 463 were positive for HBsAg (2.28 %) & 115 were positive for HCV (0.56%).  The seroprevalence for syphilis and malaria was 0.07% & 0.02% respectively. The overall  seropositivity was 3.39%. The HBsAg seroprevalence was the highest among the blood  donors.Conclusion: In order to avoid wastage of blood units, application of strict criteria for  selection and deferral of donors with emphasis on TTIs along with mandatory Nucleic Acid  Test (NAT) for screening of TTIs is required.
Keywords: Blood donors; Blood transfusions; Transfusion Transmissible Infections